Development of human-machine interfaces for stair climbing construction robot - Dipak, Bhatt Swapneel (Nanyang Technological University, 2022)
The usage of robots in various fields of the industry has been exponentially growing in recent years. One such field is construction, where robots can be used to carry out physically demanding tasks such as carrying heavy loads and transporting them around construction sites, reducing the demand for human labour to carry out this arduous task. Tele-operation of these robots is the most efficient way of utilizing them, as a fully autonomous robot in an ever-changing construction site could hinder productivity rather than benefit it. One of the most crucial aspects of tele-operation is computer vision. When operating a mobile robot, the user cannot feel safe or secure in the movement of the robot, or have complete knowledge of the direction of motion and the obstacles that lie in the path without a functioning and informative computer vision system. The ideal computer vision system on a tele-operation robot would be one that can provide the user with an experience as similar to what the user can see when driving a car as possible. To this end, it is important for computer vision systems in the human-machine interfaces on the robot to work smoothly and provide as much information to users as possible. This project is to design and integrate computer vision features for a construction site stair-climbing robot, utilizing 180° field of view fish-eye cameras. The author’s main role in this project was to design a camera system using these fish- eye cameras, develop two fields of view for the robot operator to use (wide-angle and top view) and integrate these with the robot UI. The report contains an introduction to the background and the objective of this project, followed by a detailed analysis of the experimental process, and the testing procedure. Along with this, the author’s contributions to other areas of this project will also be discussed. Finally, the limitations faced, and goals for future work will be analysed.